MEDU-04. AN OTX2-PAX GENE NETWORK REGULATES GROUP 3 MEDULLOBLASTOMA DIFFERENTIATION AND TUMOR GROWTH. (23rd April 2019) - Zagozewski, Jamie; Morrison, Ludivine; Shahriary, Ghazaleh; Stromecki, Margaret; Fresnoza, Agnes; Palidwor, Gareth; Porter, Christopher; Hawkins, Cynthia; Chan, Jennifer; Ramaswamy, Vijay; Werbowetski-Ogilvie, Tamra
Abstract: Medulloblastoma (MB) is the most common malignant primary pediatric brain tumor. Group 3 has the worst prognosis of the MB subgroups and the pathways driving Group 3 pathogenesis are poorly defined. OTX2 is overexpressed/amplified in 80% of Group 3 tumors and maintains the balance between self-renewal and neuronal differentiation. Here, we evaluated the contribution of the OTX2 gene regulatory network in driving Group 3 MB pathogenesis. We mapped changes in active (H3K4me3) and repressive (H3K27me3) histone modifications following OTX2 silencing in Group 3 MB cells. Neuronal differentiation genes encoding transcription factors (TFs) were associated with loss of H3K27me3 modifications suggesting de-repression in TF expression. Members of the PAX gene family of TFs were significantly de-repressed and their role in Group 3 MB progression is unknown. PAX3 and PAX6 expression is significantly lower in Group 3 MB patients and low expression is correlated with significantly reduced patient survival. Interestingly, OTX2 directly binds to PAX3 and PAX6 and restricts their expression in Group 3 MB cells. Over-expressing PAX3 and PAX6 in Group 3 MB cells reduced tumorsphere number, self-renewal and cell cycle properties while increasing neuronal differentiation. In addition, PAX3 expression significantly increased survival and reduced tumor size following intracerebellar transplantation. RNA-sequencing of tumorspheres over-expressing PAX3 and PAX6 revealed a reduction in Group 3 signatures including GABAergic and glutamatergic signalling. Downregulation of genes involved in mTOR signalling was specifically observed in PAX3 over-expressing tumorspheres, which may contribute to the differential survival observed in vivo . Similar changes in gene signatures were also demonstrated following OTX2 silencing in multiple Group 3 MB cell lines. Our results demonstrate that OTX2 controls cell fate decisions in Group 3 MB by regulating PAX gene expression, and that targeting downstream molecular signatures may reveal novel therapeutic targets for these highly aggressive tumors.